Utility of CK8, CK10, CK13, and CK17 in Differential Diagnostics of Benign Lesions, Laryngeal Dysplasia, and Laryngeal Squamous Cell Carcinoma - Novica Boricic; Ivan Boricic; Ivan Soldatovic; Jovica Milovanovic; Aleksandar Trivic; Tatjana Terzic (Diagnostics, 2022)
There are no reliable immunohistochemical markers for diagnosing laryngeal squamous cell carcinoma (SCC) or diagnosing and grading laryngeal dysplasia. We aimed to evaluate the diagnostic utility of CK8, CK10, CK13, and CK17 in benign laryngeal lesions, laryngeal dysplasia, and laryngeal SCC. This retrospective study included 151 patients diagnosed with laryngeal papilloma, laryngeal polyps, laryngeal dysplasia, and laryngeal SCC who underwent surgical treatment between 2010 and 2020. Immunohistochemistry (IHC) was carried out using specific monoclonal antibodies against CK8, CK10, CK13, and CK17. Two experienced pathologists performed semi-quantitative scoring of IHC positivity. The diagnostic significance of the markers was analyzed. CK13 showed a sensitivity of 100% and a specificity of 82.5% for distinguishing between laryngeal SCC and laryngeal dysplasia and benign lesions. CK17 showed a sensitivity of 78.3% and specificity of 57.1% for the detection of laryngeal SCC vs. laryngeal dysplasia. CK10 showed a sensitivity of 80.0% for discriminating between low-grade and high-grade dysplasia, and a specificity of 61.1%. Loss of CK13 expression is a reliable diagnostic tool for diagnosing laryngeal lesions with malignant potential and determining resection lines. In lesions with diminished CK13 expression, CK17 could be used as an auxiliary immunohistochemical marker in diagnosing laryngeal SCC. In CK13-negative and CK17-positive lesions, CK10 positivity could be used to determine low-grade dysplasia. CK8 is not a useful IHC marker in differentiating between benign laryngeal lesions, laryngeal dysplasia, and laryngeal SCC.